Study of the Suitability of a Personal Exposure Monitor to Assess Air Quality - Halah E. Aljofi; Thomas J. Bannan; Michael Flynn; James Evans; David Topping; Emily Matthews; DIEZ, SEBASTIÁN CESAR; Pete Edwards; Hugh Coe; Daniel R. Brison; Martie van Tongeren; Edward D. Johnstone; et al. (My University, 2024)
Low-cost personal exposure monitors (PEMs) to measure personal exposure to air pollution are potentially promising tools for health research. However, their adoption requires robust validation. This study evaluated the performance of twenty-one Plume Lab Flow2s (PLFs) by comparing its air pollutant measurements, particulate matter with a diameter of 2.5 μm or less (PM2.5), 10 μm or less (PM10), and nitrogen dioxide (NO2), against several high-quality air pollution monitors under field conditions (at indoor, outdoor, and roadside locations). Correlation and regression analysis were used to evaluate measurements obtained by different PLFs against reference instrumentation. For all measured pollutants, the overall correlation coefficient between the PLFs and the reference instruments was often weak (r < 0.4). Moderate correlation was observed for one PLF unit at the indoor location and two units at the roadside location when measuring PM2.5, but not for PM10 and NO2 concentration. During periods of particularly higher pollution, 11 PLF tools showed stronger regression results (R2 values > 0.5) with one-hour and 9 PLF units with one-minute time interval. Results show that the PLF cannot be used robustly to determine high and low exposure to poor air. Therefore, the use of PLFs in research studies should be approached with caution if data quality is important to the research outputs.
Keywords: personal monitoring tools; air pollution monitoring; air quality monitoring; commercial portable low-cost wearable sensor; portable air quality; field evaluation; public health; performance evaluation